Relation Between Dietary Carotenoid Intake, Serum Concentration, and Mortality Risk of CKD Patients Among US Adults: National Health and Nutrition Examination Survey 2001–2014 - Hu, Yuncan; Cai, Xiaoyu; Zhang, Nanhui; Li, Yu; Mao, Ya; Ge, Shuwang; Yao, Ying; Gao, Hui (Frontiers in Medicine, 2022)
Background Current evidence on the relationship between carotenoids and chronic kidney disease (CKD) patients are limited and controversial. Methods Data were obtained from the Nutrition and Health Examination Survey (NHANES) database and the NHANES Linked Mortality File, both from a nationally representative sample. Dietary intake was assessed through 24-h dietary recall, and information was available both on dietary and serum α-carotene, β-carotene, β-cryptoxanthin, lycopene, and lutein/zeaxanthin (combined) through the NHANES cycles used. We used multivariable Cox proportional hazards regression models to estimate the risk for all-cause mortality associated with carotene intakes and serum levels, adjusting for potential confounding factors. Results Of the 6,095 CKD participants, 1,924 subjects died (mean follow-up time, 8.1 years). After eliminating all the confounding factors, we found that high levels of total carotene (HR = 0.85, 95% CI, 0.75-0.97, P = 0.011) intakes at baseline were significantly associated with a lower risk of death. And the serum concentrations of carotenoid were also showing that a-carotene (HR = 0.77, 95%CI, 0.65–0.92, P = 0.002), beta-cryptoxanthin (HR = 0.83, 95%CI, 0.70–0.98, P = 0.019), lycopene (HR = 0.77, 95% CI, 0.65–0.91, P = 0.002), and lutein + zeaxanthin (HR = 0.82, 95% CI, 0.70–0.96, P = 0.002) was significantly associated with decreased all-cause mortality of CKD patients. The associations remained similar in the sensitivity analyses. Conclusion Findings suggest that high-level carotene dietary intake and the serum concentration were associated with a lower risk of mortality in the CKD population.